Innovative and sustainable membrane technology for wastewater treatment and desalination application - Goh, P.S. (Elsevier, 2019)
This chapter provides an overview on the innovative and sustainable development of membrane technology in wastewater treatment and desalination. The membrane processes based on hydraulic pressure and osmotic pressure are first outlined. The development and recent progresses made in the design and fabrication of high-performance membranes are discussed. The applications of membrane technologies in wastewater treatment, desalination, and energy generation are reviewed. Finally, the future outlook is briefly highlighted and the conclusion is drawn. Â© 2020 Elsevier Inc. All rights reserved.